POTENSI TEKNIS - EKONOMIS DAUR ULANG AIR LIMBAH INDUSTRI TEKSTIL MENGGUNAKAN APLIKASI ARANG AKTIF - Ari Christiany (Graduate School Bogor Agricultural University (SPs IPB), 2019)
Abstract.Growth Textile industry from year to year demands high creativity both design and color. The process production of textile industry especially dyeing can not separated from the use of clean water and high wastewater pollutant produced. With Zero Water Discharge principle, the industry is expected to reduce the amount of waste discharged into the environment. There are many water, and wastewater recycling technology processes. However, in Indonesia conventional wastewater processing is still widely encountered, limited to aerobic and anaerobic active sludge processes, chemical coagulation - flocculation processes, as well as activated carbon - filtration processes. This study examined the process of wastewater recycling in the management of bio-chemical waste and using activated carbon aplication for post treatment. This recycling process could improve process efficiency and saved production costs. Carbon active process decreased COD contamination up to 96%, with contact time 20 minutes. The study and research of potential wastewater recycling on conventional bio-chemical-carbon active processing expected to be an inspiration for industries, and the public to do waste water recycling.